Political Reforms and Public Policy: Evidence from Agricultural and Food Policies - Olper, Alessandro; Fałkowski, Jan; Swinnen, Johan (Oxford University Press on behalf of the World Bank, 2015)
This paper studies the effect of political regime transitions on public policy using a new data set on global agricultural and food policies over a 50-year period (including data from 74 developing and developed countries over the 1955–2005 period). We find evidence that democratization leads to a reduction of agricultural taxation, an increase in agricultural subsidization, or both. The empirical findings are consistent with the predictions of the median voter model because political transitions occurred primarily in countries with a majority of farmers. The results are robust to different specifications, estimation approaches, and variable definitions.